Advances in Intelligent Data Analysis IX 9th International Symposium, IDA 2010, Tucson, AZ, USA, May 19-21, 2010. Proceedings - Cohen, Paul R.; Adams, Niall M.; Berthold, Michael R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 9th International Conference on Intelligent Data Analysis, IDA 2010, held in Tucson, AZ, USA in May 2010. The 21 revised papers presented together with 2 invited papers were carefully reviewed and selected from more than 40 submissions. All current aspects of intelligent data analysis are addressed, particularly intelligent support for modeling and analyzing complex, dynamical systems. Topics covered are end-to-end software systems; modeling complex systems such as gene regulatory networks, economic systems, ecological systems, resources such as water, and dynamical social systems such as online communities; and robustness, scaling properties and other usability issues.
Changing the Focus of the IDA Symposium -- Changing the Focus of the IDA Symposium -- Invited Papers -- Graph Identification -- Intelligent Data Analysis of Intelligent Systems -- Selected Contributions -- Measurement and Dynamical Analysis of Computer Performance Data -- Recursive Sequence Mining to Discover Named Entity Relations -- Integration and Dissemination of Citizen Reported and Seismically Derived Earthquake Information via Social Network Technologies -- Detecting Leukaemia (AML) Blood Cells Using Cellular Automata and Heuristic Search -- Oracle Coached Decision Trees and Lists -- Statistical Modelling for Data from Experiments with Short Hairpin RNAs -- InfraWatch: Data Management of Large Systems for Monitoring Infrastructural Performance -- Deterministic Finite Automata in the Detection of EEG Spikes and Seizures -- Bipartite Graphs for Monitoring Clusters Transitions -- Data Mining for Modeling Chiller Systems in Data Centers -- The Applications of Artificial Neural Networks in the Identification of Quantitative Structure-Activity Relationships for Chemotherapeutic Drug Carcinogenicity -- Image Approach towards Document Mining in Neuroscientific Publications -- Similarity Kernels for Nearest Neighbor-Based Outlier Detection -- End-to-End Support for Dating Paleolandforms -- Spatial Variable Importance Assessment for Yield Prediction in Precision Agriculture -- Selecting the Links in BisoNets Generated from Document Collections -- Novelty Detection in Projected Spaces for Structural Health Monitoring -- A Framework for Path-Oriented Network Simplification -- A Data-Driven Paradigm to Understand Multimodal Communication in Human-Human and Human-Robot Interaction -- Using CAPTCHAs to Index Cultural Artifacts.
Keywords: Computer science; Computer software; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Database Management; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity